The Effectiveness of Educational Game Learning Media “APAN” on Learning Outcomes of 5th Grade Elementary School Students - Tazkiyah, Riska Aida; Utama, Candra; Winahyu, Sri Estu (Proceedings Series of Educational Studies, 2024)
Research on the effectiveness of educational game learning media “APAN” on the learning outcomes of fifth grade elementary school students has been carried out and tested on 46 fifth grade students of SDN Kalirejo, using a Quasi Experimental Design research design and research design using Nonequivalent Control Group Design. The population in this study amounted to 66 students spread over 3 parallel classes and the research sample amounted to 46 students taken with simple random sampling technique. Data collection through tests. Data analysis used the Paired Samples t-Test and Independent Samples t-Test tests which had been tested for the prerequisite assumptions of normality and homogeneity of the data. The results of the Paired Samples t-Test test obtained a p-value